Epicatechin ameliorates palmitate-induced insulin resistance in C2C12 myogenic cells by alleviating oxidative stress and activating the AMPK/ACC pathway - Ling Song; Kailan Huang; Di Tian; Xinhui Liu; Rong Huang; Jiaxing Luo; Ming Zhang; Juan Lu; Mingying Gui; Xiao Ma (CyTA - Journal of Food)
Epicatechin (EC) is a water-soluble natural organic compound belonging to the flavanol class of compounds. It exhibits various physiological activities such as anti-inflammatory, antioxidant, treatment of mitochondrial diseases, and prevention of cardiovascular diseases.To examineEC’s impact and mechanism on adult myoblasts’ insulin resistance. The effects of various EC concentrations on the viability of C2C12 adult myoblasts were measured, as were glucose consumption and glycogen content; in vitro antioxidant activity of EC was measured; cellular oxidative marker content and apoptosis were measured; and protein expression was detected by Western blot. A model of insulin resistance in C2C12 myogenic cells was established using palmitic acid. EC significantly increased the glucose consumption and glycogen content; EC increased the levels of CAT, SOD and GSH and decreased the levels of NO, MDA and ROS; EC decreased the apoptosis rate of cells; EC treatment upregulated the levels of GLUT4, p-AMPK, p-ACC, NRF2, and HO-1 proteins. These results suggest that EC can regulate the NRF2/HO-1 signaling pathway, enhance GLUT4 transport, activate AMPK/ACC pathway, enhance cellular uptake of glucose, thus effectively improving insulin resistance in C2C12 cells.